Barriers to early diagnosis and treatment of cervical cancer in Addis Ababa, Ethiopia: qualitative study - Alem Gebremariam; Adamu Addissie; Alemayehu Worku; Mathewos Assefa; Eva Johanna Kantelhardt; Ahmedin Jemal; Nebiyu Dereje (BMJ Open)
Objective Cervical cancer remains the most diagnosed and deadly cancer among women in low and middle income countries, including Ethiopia, although it can be controlled if detected and treated early. However, research on contextual barriers to early diagnosis and treatment of cervical cancer is limited in Ethiopia. This study aimed to describe the lived experience of the patients and to explore the barriers to early diagnosis and treatment of cervical cancer.Design We conducted a phenomenological qualitative study, which was part of a larger mixed-methods study.Setting Tikur Anbesa Specialised Comprehensive Hospital, Addis Ababa, Ethiopia.Participants 24 purposively selected patients with diagnostic delay and 16 patients with treatment delay were interviewed using an in-depth interview guide (IDI).Results Two broad themes and seven sub-themes to explain the barriers to early diagnosis and treatment of cervical cancer emerged. These themes and sub-themes include patient related barriers (inadequate knowledge, visits to traditional healers and practice of religious rituals as a solution for illness, poor adherence to the treatments and fear of side effects, and financial hardships) and provider related barriers (limited access to diagnostic and treatment infrastructure, inadequate training of healthcare providers and poor quality of care).Conclusions The findings of the study underscore the need to reinforce awareness among patients and the community, scale up the screening, diagnostic and treatment infrastructure, and advocate for quality of care in the healthcare facilities in Ethiopia to promote early diagnosis and treatment of cervical cancer.